Random Amplified Polymorphic DNA Typing of Clinical and Environmental Aeromonas hydrophila Strains from Limpopo Province, South Africa (Journal of Health, Population and Nutrition, 2010)
p>The aim of the present study was to determine the genetic relatedness of strains isolated from diarrhoeal stool and water specimens collected from water-storage containers from different geographical areas in the Limpopo province. In total, 32 Aeromonas strains isolated from stool specimens collected from HIV/AIDS patients suffering from gastroenteritis and their household drinking-water stored in 20-L and 25-L containers were analyzed by random amplified polymorphic DNA PCR (RAPD). The RAPD fingerprints obtained proved reproducible when repeated on three different occasions using whole-cell DNA isolated from the Aeromonas strains. In total, 12 unique RAPD fingerprints were found. The results revealed a tendency of the isolates to cluster according to their origin of isolation (best-cut test 0.80 and bootstrap values >50%). However, a certain degree of similarity was also observed between isolates of water sources and clinical sources which indicated genetic relatedness. There were also genetic similarities between the clinical and the environmental strains of Aeromonas spp. isolated from different geographical areas. This study has demonstrated the genetic relatedness of Aeromonas hydrophila isolates from household drinking-water and clinical sources in South Africa, which may be due to cross-contamination from water to patients or vice-versa. This observation is of public-health significance, particularly in the era of HIV/AIDS. This study points to the importance of monitoring and evaluating infection-control measures for improved hygiene and to prevent cross- contaminations.Key words: Aeromonas; Aeromonas hydrophila; Diarrhoea; Genotyping; South AfricaDOI: 10.3329/jhpn.v28i1.4517 J Health Popul Nutr 2010 Feb; 28(1): 1-6